Factors influencing the choice of a university degree: the case of physical activity, recreation and sport tourism studies - Çitozi, Robert; Mara, Ferdinand; Bozo, Spartak (Arena-Journal of Physical Activities, 2018)
The aim of this research is to analyse studentsÂ´ expectations that have an influence on choosing Physical Activity, Recreation and Sport Tourism as an academic major. According to the analysis of this research on the reasons for choosing Fitness, Recreation and Sport Tourism studies at Sports University of Tirana, the conclusions reached show that among multiple factors, the expectations of having collaborative and situated learning experiences are one of the main reasons for choosing these studies, as well as the a lot of job opportunities that this degree offers. Methods and subjects. The final cohort involved in this study was comprised of 320 students, of whom 35.94% were women and 64.06% men. Almost half of the participants (48%) were aged between,18-20 and 39% were aged between, 21-22. This article explores the expectations that have driven students in their choice of a Leisure and Recreation academic major, considering that if the studies match the expectations of the students, the probability of success in the learning process will increase. With this conceptual framework in mind, the following research questions have been developed: 1.What are the studentÂ´s curriculum and job expectations for choosing RFST studies? 2. In which degree can situated and collaborative learning be found among those expectations? The third researchÂ question refers to the level of rationality or emotionality that emerges in the expression of the expectations. Results. Over 92% of the participants were full-time students and 8% were part-time students. Participants are coming to follow studies in FPAR (36.67%), for fitness instructor, (25.14%) sport tourism guide, 13.12% rehabilitation sciences, (11.92%) touristic animator and (13.15%) other specialities.